Cavitation-enhanced delivery of a self-amplifying oncolytic adenovirus for tumour-selective cancer therapy. - Carlisle, R; Choi, J; Seymour, L; Coussios, C (2012)
Unlike conventional gene therapy, oncolytic adenoviruses selectively infect and replicate within cancer cells, potentially enabling systemically administered yet highly targeted self-amplifying cancer therapy. Until recently, therapeutic efficacy was hindered by limited extravasation of the virus to poorly vascularized tumour regions and by liver toxicity beyond a certain dose. In the present work, co-injection of the virus with contrast agent microbubbles (SonoVue) and exposure of the tumour to ultrasound using a set of optimized parameters (0.5 MHz, peak rarafactional pressure 1.2 MPa, pulse length 50,000 cycles, pulse repletion frequency 0.5 Hz) result in inertial cavitation, which is found to enable increased extravasation and improved distribution of the virus throughout the tumour. Stealthing of the virus using a novel polymer coating results in improved circulation times, yielding a 30-fold increase in tumour viral expression at 3 days relative to delivery without ultrasound. Post-injection survival of mice bearing subcutaneous human breast cancer cell tumours (ZR75.1) of initial volume in excess of 30 mm3 is extended from 22-42 days for the virus alone to 22-80 days in the presence of inertial cavitation (n=7). Ultrasound-enhanced delivery mediated by inertial cavitation is thus expected to play a key role in the clinical application of oncolytic virotherapy.